2007
DOI: 10.1007/s10750-007-9164-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting denitrification in agricultural headwater streams in Northeast Ohio, USA

Abstract: As a result of increased anthropogenic nitrogen (N) loading in surface waters of agricultural watersheds, there is enhanced interest to understand and quantify N removal mechanisms. Denitrification, an important N removal mechanism in aquatic systems, may contribute to reducing N pollution in agricultural headwater streams. However, the key factors controlling this process in lotic systems remain unclear. The objective of our study was to examine the factors regulating rates of denitrification in the sediments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 46 publications
3
29
0
Order By: Relevance
“…5a). Although the saturation equation is used commonly to describe enzymatic limitation on reaction rates in homogeneous systems, and it has been used to describe nutrient uptake rates in streams (Garcia-Ruiz et al 1998b;Payn et al 2005;Opdyke and David 2007;Herrman et al 2008), there is not necessarily a direct link between these different applications, and a mechanistic model for this relation may be complex for systems with benthic gradients and(or) hyporheic flow.…”
Section: Reach-scale Controls On Benthic Denitrificationmentioning
confidence: 99%
See 1 more Smart Citation
“…5a). Although the saturation equation is used commonly to describe enzymatic limitation on reaction rates in homogeneous systems, and it has been used to describe nutrient uptake rates in streams (Garcia-Ruiz et al 1998b;Payn et al 2005;Opdyke and David 2007;Herrman et al 2008), there is not necessarily a direct link between these different applications, and a mechanistic model for this relation may be complex for systems with benthic gradients and(or) hyporheic flow.…”
Section: Reach-scale Controls On Benthic Denitrificationmentioning
confidence: 99%
“…e Estimated values of k1 denit calculated from v f,denit /depth; depth was calculated from Q using the empirical relation (Leopold and Maddock 1953) Herrman et al 2008). Temperature effects include changes in microbial community structure and biomass, as well as thermal effects on enzymatic processes, resulting in complex functions with effective q10 values ranging from around 1 (no temperature effect) to 2 (doubling the rate for 10°C increase in T) or more (e.g., Herbert and Nedwell 1990), where q10 is defined by: rate T /rate 20 = q10 [(T-20)/10] , with T, 10, and 20 in°C.…”
Section: Hypothetical Models Of Temporal Variations In Denitrificationmentioning
confidence: 99%
“…Previous studies have demonstrated that N 2 O production and emission from diverse rivers respond significantly to increasing anthropogenic N loading (Cole and Caraco, 2001;Garnier et al, 2006). Numerous investigations have reported strong correlations between dissolved N 2 O and NO 3 -concentration in river waters (Herrman et al, 2008;Silvennoinen et al, 2008). Yan et al (2012) concluded that NO 3 -is a valid predictor of river N 2 O production in a large-deep river.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the bulk nitrogen isotope values passed the mass conservation test for all of the sampling sites (Table 2). It is, nevertheless, important to recognise that nitrogen isotopic fractionation can be induced by a number of processes including nitrification, denitrification, nitrogen fixation and assimilation (Montoya and McCarthy, 1995;Lehmann et al, 2002;Hantush, 2007;Herman et al, 2008). On this basis, the tendency for transformations of bulk isotope fingerprints during fluvial transport warrants further work (Kendall et al, 2001;Fox et al, 2010).…”
mentioning
confidence: 99%